VD_FINDINFO Décision / 2015 / 643 vom 27. August 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, RISQUE DE COMMISSION | 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 222 CPP (CH), 393 al. 1 let. c CPP (CH)